Global Longitudinal Strain in master athletes and in hypertensive patients with the same degree of septal thickness. (17th October 2016) - D'Elia, E.; Ferrero, P.; Vittori, C.; Calabrese, A.; Duino, V.; Perlini, S.; Senni, M.
Abstract : Athletes may have electrocardiogram (ECG) repolarization abnormalities during stress test suggestive for ischemia in the absence of ischemic coronary artery disease, often in a setting of myocardial septum hypertrophy. Global longitudinal strain (GLS) might be altered in these athletes compared to hypertensive patients with the same degree of septal thickness. About 735 consecutive athletes were screened for mandatory assessment of fitness to participate in competitive sports. At the stress test, 23 (19 M, 4 F) were found to have ECG repolarization abnormalities suggestive for ischemia in the presence of normal coronary vessels. They were matched to a control group of 23 hypertensive patients with no ECG abnormalities during stress test and the same degree of septal thickness. A transthoracic echocardiography for evaluation of global longitudinal strain (GLS) was performed. Interventricular septum thickness (IST) and relative wall thickness (RWT) were also calculated. A preserved ventricular function was seen in both groups (64 ± 8% in cases vs 60 ± 6% in controls, P = 0.42). IST and RWT were not significantly different. GLS was significantly lower in athletes vs hypertensive patients (−18.7 ± 2.5 vs −21.67 ± 0.27, P = 0.001). In athletes with septal hypertrophy and a positive stress test not associated to coronary disease, GLS is lower with respect to a population of hypertensive patient with the same degree of septal hypertrophy. Further investigations in a larger population are required to better define the potentiality of GLS in differentiating pathological vs physiological septum hypertrophy.